1999
DOI: 10.1002/(sici)1521-3765(19991001)5:10<2877::aid-chem2877>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinic Peptide Matrix Metalloproteinase-9 Inhibitors by Solid-Phase Synthesis Using a Building Block Approach

Abstract: The solid-phase synthesis of an array of different pseudopeptides containing a phosphinic glycine ± leucine moiety (-GY{P(O)OH-CH 2 }L-) [1] is described. The resulting pseudopeptides were shown to act as matrix metalloproteinase-9 (MMP-9) inhibitors. Starting from available materials, the protected amino acid isosters benzyloxycarbonyl aminomethylphosphinic acid (glycine analogue) and ethyl a-isobutylacrylate (leucine analogue) were synthesized and coupled with the bis(trimethylsilyl)phosphonite. Protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 47 publications
2
46
0
5
Order By: Relevance
“…Recombinant mouse full length pro-MMP-9 was expressed in BHK cells and subsequently purified from the conditioned medium [22]. Recombinant rabbit MMP-14 catalytic domain was cloned from rabbit osteoclasts [29] and purified from the supernatant of transfected E. coli cells (Ovejero, M.C, Lenhardt, T. and Ferreras, M. unpublished data).…”
Section: Methodssupporting
confidence: 60%
“…Recombinant mouse full length pro-MMP-9 was expressed in BHK cells and subsequently purified from the conditioned medium [22]. Recombinant rabbit MMP-14 catalytic domain was cloned from rabbit osteoclasts [29] and purified from the supernatant of transfected E. coli cells (Ovejero, M.C, Lenhardt, T. and Ferreras, M. unpublished data).…”
Section: Methodssupporting
confidence: 60%
“…mp, 95-96 8C. 24 The second component, N-acryloylglycinate 2 was obtained using the mixed anhydride procedure. This accomplished the activation of acrylic acid (1.44 g, 0.02 mol) to the corresponding anhydride by means of isobutyl chloroformate (2.72 ml, 0.021 mol) in the presence of N-methylmorpholine (2.33 ml, 0.021 mol) in anhydrous THF (20 ml) at 0 8C.…”
Section: Hplc-based Activity Assaymentioning
confidence: 60%
“…21,22 Then, the adduct was hydrolysed in acidic conditions and the obtained amino acid was N-protected with benzyl chloroformate in basic conditions as described in the literature. 23,24 The overall yield of the procedure was 45%. Mp, 90-91 8C (colourless crystals recrystallized from ethyl acetate/toluene), lit.…”
Section: Hplc-based Activity Assaymentioning
confidence: 99%
“…810 But our initial attempt of Michael-type addition of Fmoc-protected aminomethyl phosphinic acid and electron deficient acrylate was not successful. 8,11 Thus, Cbz-protected aminomethyl phosphinic acid 3 was converted to its trivalent state by the action of HMDS and subsequently reacted with an α -isopropyl- α , β -unsaturated ester 12 to give product 4 in good yield (Scheme 1). However, as will be described subsequently, the Cbz group is very efficiently exchanged for Fmoc in the final step of the synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meldal and coworkers, Yiotakis et al, and Yokomatsu and coworkers reported the synthesis of different phosphinate dipeptide building blocks by using a procedure involving the Michael addition of variously protected aminomethyl phosphinic acids to an acrylic acid ester followed by protecting group manipulation to afford the desired product. 8 Using a creative variation of these methods, FmocNHCH 2 PO(OAd)-CH 2 CH(Pr i )CO 2 H ( 1a , Scheme 2) was prepared and subsequently incorporated into a triple-helical sequence, resulting in a construct, which exhibited potent and selective inhibition of MMP-2 and MMP-9. 7 However, this previously described synthetic route to 1a required a low yielding (35%) and problematic final step involving a Ru-catalyzed deprotection of an allyl ester.…”
Section: Introductionmentioning
confidence: 99%